2019
DOI: 10.21776/ub.jam.2019.017.01.20
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corporate Governance, Corporate Social Responsibility, Firm Size on Firm Value: Financial Performance as Mediation Variable

Abstract: This study aims to examine and analyze the effect of directly or indirectly between the variables of corporate governance, corporate social responsibility, firm size, the financial performance of the company with the sample value amounted to 53 companies engaged in the manufacturing sector with years of observations from 2015 to 2017. Methods of data analysis using path analysis with AMOS software 24. Corporate governance is proxied by the Corporate Governance Index (CGI), corporate social responsibility is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
5
8
1
4
Order By: Relevance
“…The findings of this study strengthen the studies conducted by Servaes and Tamayo (2013);Astuti et al (2018); Laili et al (2019); Amato and Falivena (2019); Seok et al (2019); Kamaliah (2020); Hendratama and Huang (2021) which concluded that CSR disclosure promotes better firm value, indicating that the more social disclosure items and the better the quality of the disclosure, the greater the firms' value.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of this study strengthen the studies conducted by Servaes and Tamayo (2013);Astuti et al (2018); Laili et al (2019); Amato and Falivena (2019); Seok et al (2019); Kamaliah (2020); Hendratama and Huang (2021) which concluded that CSR disclosure promotes better firm value, indicating that the more social disclosure items and the better the quality of the disclosure, the greater the firms' value.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, Naseem et al (2017) uncovered causality between CSR disclosure and company performance in China. With respect to Indonesia, Laili et. al (2019) and Kamaliah (2020) found that CSR disclosure positively influences the value of Indonesian manufacturing sectors.…”
Section: Introductionmentioning
confidence: 99%
“…This two-way relationship in CSR and financial performance has proven to be positive. This is also confirmed by research conducted by Arsoy et al (2012), Hafez (2016), Ilmi et al(2017), Jallo andMus (2017), Firdaus et al, (2018), Maqbool and Zameer (2018), Laili et al (2019), Javeed and Lefen (2019) and Cho et al (2019) where they show that CSR activities carried out by companies have a positive impact on improving financial performance. The results of research conducted by Chetty et al (2015), Madorran and Garcia (2016), and Mansaray et al (2017) meanwhile prove otherwise, where CSR does not affect company performance.…”
Section: Corporate Social Responsibility and Financial Performancesupporting
confidence: 75%
“…In an agency relationship, there is a contract where a principal employs an agent to perform duties under their names, including delegating authority in decision-making (Jensen & Meckling, 1976). With the authority given to the agent, they are expected to make the best decision for the interest of the principal (Laili et al, 2019). However, the interests of the principal and the agent are often in conflict with each other, leading to the agency problem (Haryanti, 2019).…”
Section: Agency Theorymentioning
confidence: 99%
“…This is in line with the study done by Ammann et al, (2011), Javaid (2015 & Owusu & Weir (2016) which shows that good governance has a positive impact on value creation, which means that a company that is able to implement good corporate governance are more likely to have higher company value. However, in a study conducted by Laili et al, (2019), it is found that corporate governance has no significant impact on financial performance and company value.…”
Section: Introductionmentioning
confidence: 95%